The cultural novice: writing oneself into knowing with memoir and poetry. Issue 4 (1st October 2016) - Scott, Joy Denise
ABSTRACT: This essay explores my professional and personal encounters with a class of Chinese students, foregrounding one relationship in particular, to reveal the intricacies of teacher and student relations within a Shanghai university setting. I use memoir countered by poetic narratives to disrupt essentialist representations, found in much of the transnational scholarly literature, which frames Chinese students as passive learners. Taking an interventionist approach I play with spoken and written words to craft free-flowing poetry that articulate my interpretation of solitary and collective Chinese voice/s. In pulling apart their words, I imagine myself as embroiderer, blending and entwining together strands of words to create a braided narrative of memoir and poetry that performs as a provocative rhetorical device; writing that reveals my emotional angst, frustration and moral indignation and, from a witness's perspective, my interpretation of the feelings of my Chinese students.